Overview of Islamic Financial System and its Efficiency - Nakhavali, Miad (European Scientific Journal, ESJ, 2017)
This essay attempts to discuss the principles of Islamic financial system based on Sharia law and its efficiency in the real world. It is achieved by overlooking different methods of Islamic financial and banking system. The focus of the essay is on the examination of Islamic financial system and its approaches in the Islamic countries, especially those shariabased law countries. Sharia law is based on the Holy Book of Muslims Quran and on the traditional teaching of Prophet Muhamad in the so called Sunnah. Even the most restricted Islamic banks are using conventional banking methods under the cover of Islamic slogans. Despite these methods, the share of Islamic banks when compared with conventional ones is extremely low. The other inefficacy of Islamic banks involves reducing customer’s freedom by prohibiting all interest-methods and giving them some dictated options only.